Pengibaran Bendera One Piece dan Produksi Musuh Imajiner: Pendekatan Kriminologi Kritis atas Politik Ketakutan - zulkhaidirkadir (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The state has a mandate to guarantee citizens' freedom of expression by protecting symbolic representations in public spaces. However, legal construction in Indonesia tends to use the law as a tool to limit visual interpretation, including popular cultural symbols such as the One Piece flag. This study aims to explain two main aspects of the mechanism of symbol criminalization: the state's construction of symbols as threats without any basis in actual violations, and the political use of fear through the production of imaginary enemies. The research method employed a qualitative approach with a conceptual approach. The results show that the state's interpretation of visual symbols rests not on the legality of the action, but on controlling the potential meanings that develop outside the official narrative. Within this construction, the law operates as a filtering mechanism for forms of articulation deemed inconsistent with the state's ideological interests. This strategy shifts the focus from concrete violations to the surveillance of social imagination. Thus, the criminalization of symbols occurs not because of their factual content, but because they open up pathways of solidarity that cannot be institutionally controlled. A critical criminological approach demonstrates that the state uses the law to enforce symbolic domination through techniques of controlling meaning within a democratic regime that formally promises freedom of expression.